The Norton history of the human sciences - Smith, Roger, 1945- (New York : W.W. Norton, 1997)
This book is a comprehensive history of the human sciences--psychology, sociology, anthropology, economics, and political science--from their precursors in early human culture to the present. This accessible volume in Norton's History of Science series tracks the long and circuitous path by which human beings came to see themselves and their societies as scientific subjects like any other. Beginning with the Renaissance's rediscovery of Greek psychology, political philosophy, and ethics, Roger Smith recounts how the human sciences gradually organized themselves around a scientific conception of psychology, and how this trend has continued to the present day in a circle of interactions between science and ordinary life, in which the human sciences have influenced and been influenced by popular culture.
Pt. I. Introduction. 1. The History of the Human Sciences -- Pt. II. The 16th and 17th Centuries. 2. The Dignity of Man. 3. The Province of Natural Law. 4. Body and Soul -- Pt. III. The Long 18th Century. 5. John Locke and the Natural History of the Soul. 6. The Principles of Rational Science. 7. Human Nature: Natural and Moral Philosophy. 8. Human Diversity and Sociability. 9. Political Economy. 10. Culture of the Spirit -- Pt. IV. The 19th Century. 11. Academic Disciplines and Public Values. 12. The Science of Society: Auguste Comte and Karl Marx. 13. Human Evolution. 14. The Academic Disciplines of Psychology. 15. The Academic Disciplines of Sociology -- Pt. V. Psychologies in the 20th Century. 16. Psychological Society. 17. Natural Science and Objectivity. 18. The Unconscious: Reason and Unreason. 19. The Individual and the Social. 20. The Past and the Present.
Originally published: The Fontana history of the human sciences. London : Fontana, 1997.
Includes bibliographical references (p. [871]-1008) and index.
Keywords: Social sciences -- History; Social Sciences -- history; Geschichte 1500-1997